Passengers [videorecording (Blu-Ray)] - Spaihts, Jonathan; Pratt, Chris, 1979-; Lawrence, Jennifer, 1990-; Sheen, Michael; Fishburne, Laurence, III, 1961-; Garcia, Andy; Newman, Thomas, 1955-; Prieto, Rodrigo (Sony Pictures Home Entertainment, 2017)
Two passengers board a spaceship transporting them to a new life on another planet. The trip takes a deadly turn when their hibernation pods mysteriously wake them 90 years before they reach their destination. As Jim and Aurora try to unravel the mystery behind the malfunction, they begin to fall for each other, unable to deny their intense attraction, only to be threatened by the imminent collapse of the ship and the discovery of the truth behind why they woke up.